The investigation on the impact of financial crisis on Bursa Malaysia using minimal spanning tree - Bahaludin, Hafizah; Abdullah, Mimi Hafizah; Lam, Weng Siew; Lam, Weng Hoe (2019)
In recent years, there has been a growing interest in financial network. The financial network helps to visualize the complex relationship between stocks traded in the market. This paper investigates the stock market network in Bursa Malaysia during the 2008 global financial crisis. The financial network is based on the top hundred companies listed on Bursa Malaysia. Minimal spanning tree (MST) is employed to construct the financial network and uses centrality measurements such as degree, betweenness, closeness and eigenvector centrality. The results indicate that there are some changes on the linkages between securities after the financial crisis, that can have some significant effect in investment decision making.